Bridging Structural Inhomogeneity to Functionality: Pair Distribution Function Methods for Functional Materials Development. Issue 6 (22nd January 2021) - Zhu, He; Huang, Yalan; Ren, Jincan; Zhang, Binghao; Ke, Yubin; Jen, Alex K.‐Y.; Zhang, Qiang; Wang, Xun‐Li; Liu, Qi
Abstract: The correlation between structure and function lies at the heart of materials science and engineering. Especially, modern functional materials usually contain inhomogeneities at an atomic level, endowing them with interesting properties regarding electrons, phonons, and magnetic moments. Over the past few decades, many of the key developments in functional materials have been driven by the rapid advances in short‐range crystallographic techniques. Among them, pair distribution function (PDF) technique, capable of utilizing the entire Bragg and diffuse scattering signals, stands out as a powerful tool for detecting local structure away from average. With the advent of synchrotron X‐rays, spallation neutrons, and advanced computing power, the PDF can quantitatively encode a local structure and in turn guide atomic‐scale engineering in the functional materials. Here, the PDF investigations in a range of functional materials are reviewed, including ferroelectrics/thermoelectrics, colossal magnetoresistance (CMR) magnets, high‐temperature superconductors (HTSC), quantum dots (QDs), nano‐catalysts, and energy storage materials, where the links between functions and structural inhomogeneities are prominent. For each application, a brief description of the structure‐function coupling will be given, followed by selected cases of PDF investigations. Before that, an overview of the theory, methodology, and unique power of the PDF method will be also presented. Abstract : The pair distribution function (PDF) applications in a range of functional materials is reviewed. The outlines of principle, methodology, and unique powers of this technique have been firstly presented, followed by an introduction of its applications on selected functional material areas. Throughout this review, it has been attempted to emphasize the interplay between short‐range inhomogeneities and functionalities in novel functional materials.